Atividade ovicida in vitro de Pleurotus ostreatus var. florida sobre Ancylostoma sp. e Toxocara canis - Oliveira, Dionatan Teixeira de (2019)
Companion animals are plagued by a multitude of parasitic diseases. Among them are the infections caused by hookworms and ascarids, as these are responsible for a high death rate of dogs and cats, especially in the initial phase of life. In addition, parasites of the genus Toxacara and Ancylostoma present great veterinary medical importance, as they are agents of zoonoses "Larva migrans visceral" and "Larva migrans cutaneum", respectively. Many researches are being developed in order to minimize the damages associated with these parasites, however, an area not yet explored is related to natural products. The fungi of the genus Pleurotus are highly requested in the international market, with gastronomic and medicinal applications, but their nematicidal activities on carnivorous nematodes have not yet been reported. In search of this, approximately 1000 eggs of Ancylostoma spp. were poured into 6-well culture plates, and a solution with different concentrations of the aqueous extract of Pleurotus ostreatus var. florida (50%, 25%, 12.5%, 6.25%, 3.12%). The plates were incubated for 48 h at 26 ° C, and after the period, larval hatching was performed. In the second experiment 1,000 Toxocara canis eggs were poured into 6-well culture plates and the same concentrations of the aqueous extract were applied and incubated at 26 ° C for 21 days. Every 7 days, the egg embryo evolution was classified. In both experiments the negative control was composed only of solution with eggs and distilled water. Triplicates were performed in all groups of each test. In the test with Ancylostoma spp., There was a percentage of reduction of hatchability up to 67.16% in relation to the control, and the concentration of 3.12% was the highest percentage of hatchability of larvae among the tested concentrations. In the experimental trial with Toxocara canis eggs, all concentrations were effective in the reduction of larval eggs from the fourteenth day of evaluations. Pleurotus ostreatus var. florida showed to have a good ovicidal activity both on Ancylostoma spp. eggs and on Toxocara canis eggs, demonstrating a great potential in the biological control of the nematode.